2017
DOI: 10.3389/fpsyg.2017.01189
|View full text |Cite
|
Sign up to set email alerts
|

School Achievement and Performance in Chilean High Schools: The Mediating Role of Subjective Wellbeing in School-Related Evaluations

Abstract: School achievement gaps and school failure are problematic issues in Latin America, and are mainly explained by the socio-economic status (SES) of the students. What schools can do to improve school achievement and reduce school failure is a critical issue, both for school management and teacher training. In this study, we present the association of individual and school-related socio-emotional variables with school achievement and performance, controlling for the effects of SES. A probabilistic sample of 4,96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 73 publications
(91 reference statements)
0
34
0
5
Order By: Relevance
“…It was observed that 68.4% of the youngest people between 15 and 17 years old were attending school at the correct age and there were only 31.7% of people aged 18 to 24 years in this situation in 2017 22 . These findings indicated that there were important disparities in school failure in adolescents associated with demographic and social demands as they grow older, such as having to work, having to take care of household chores or even losing interest in studying 2 , 3 , 22 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It was observed that 68.4% of the youngest people between 15 and 17 years old were attending school at the correct age and there were only 31.7% of people aged 18 to 24 years in this situation in 2017 22 . These findings indicated that there were important disparities in school failure in adolescents associated with demographic and social demands as they grow older, such as having to work, having to take care of household chores or even losing interest in studying 2 , 3 , 22 .…”
Section: Discussionmentioning
confidence: 96%
“…School failure was the outcome variable of the study and was evaluated by the following question: “Up to which grade did you study?” The answers were converted into years of study considering the first year of elementary school and repetitions 2 , 3 , 6 . To differentiate adolescents with at least two years of delay with regard to progress expected by age, the criterion of 11 years of studies was adopted for adolescents 18 to 19 years; 10 for those aged 17; 9 for those aged 16; and 8 for those aged 15, as performed in the study by Barbato et al (2009) 21 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These characteristics increase the inequality among students, which initially is originated by a well-known socioeconomic status gap. Indeed, the Chilean educational system estimates the school vulnerability index (SVI), which is an indicator of the degree of educational establishment vulnerability (ranging from 0 to 100, indicating what percentage of students presents in an unfavourable socioeconomic status and therefore, they become priority for the government policies) [38]. Despite the above the Chilean education system is one of the highest-performing in Latin-America but it also presents one of the highest within-country variability in outcomes [39].…”
Section: Introductionmentioning
confidence: 99%